Antibody responses in chickens experimentally infected with low and high passaged chicken anemia virus isolates - Chowdhury, Shah Md. Ziqrul Haq; Omar, Abdul Rahman; Ideris, Aini; Darus, Azizah; Kono, Yuji (Veterinary Association Malaysia, 2005)
It has been shown that chicken anemia virus (CAV) which had undergone 60 and 123 passages in cell cultures (SMSC-1IP60, SMSC-I/P123, 3-1IP60 and 3-l/P123) were less pathogenic compared to low passaged CAY (SMSC- 1 and 3-1) isolates. In this study, the ability of the isolates to induce antibody responses was studied using enzymelinked immunosorbent assay (ELISA). All the isolates regardless of the number of cell culture passages that they had undergone elicited CAY antibody responses both at 16 and 30 days post inoculation. A CAY isolate, BL-5 that was not passaged in cell culture elicited higher antibody response than the cell culture passaged isolates. However, the differences in the average ELISA titres and the percentage of positive sera between the isolates were not statistically significant (P>0.05). The study showed that CAY isolates which had undergone repeated passages in cell culture are still immunogenic